2004
DOI: 10.1002/humu.9247
|View full text |Cite
|
Sign up to set email alerts
|

Familial melanoma, pancreatic cancer and germline CDKN2A mutations

Abstract: Germline CDKN2A mutations have been observed in approximately 20 percent of familial melanoma kindreds from North America, Europe and Australasia. There is also an increased risk of pancreatic cancer in a subset of families with mutations, however, the precise relationship between the CDKN2A gene and pancreatic cancer remains unknown. The relationships between familial melanoma, pancreatic cancer and germline CDKN2A mutations were examined using published data. There were 67 different CDKN2A mutations in 189 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 74 publications
2
86
1
4
Order By: Relevance
“…25 However, one smaller study of 23 families with familial pancreatic cancer revealed two truncating mutations (both in families also affected by melanoma) affecting p16 but none in p14ARF. 3 With regard to the type of mutation in CDKN2A, one previous report suggests that splicing mutations were more common in melanoma families affected with pancreatic cancer than in those without (17 vs 5% of mutations), 29 however, the underlying reason for an individual developing pancreatic cancer rather than melanoma is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, one smaller study of 23 families with familial pancreatic cancer revealed two truncating mutations (both in families also affected by melanoma) affecting p16 but none in p14ARF. 3 With regard to the type of mutation in CDKN2A, one previous report suggests that splicing mutations were more common in melanoma families affected with pancreatic cancer than in those without (17 vs 5% of mutations), 29 however, the underlying reason for an individual developing pancreatic cancer rather than melanoma is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Ala148Thr is considered a p16 polymorphism and not a pathogenic mutation. Genetic mutations at the CDKN2A gene have been identified in 20% of melanoma families, most of these in exons 1a and 2 (Goldstein, 2004). Several studies also implicated the ARF gene as underlying melanoma predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…The p14 ARF protein is also involved in cell cycle regulation by interacting with different substrates in the p53 pathway , and by binding to MDM2, also in the Rb pathway with resultant cell cycle arrest in both G1 and G2 phases (Xiao et al, 1995;Weber et al, 1999;Momand et al, 2000). In all, 20% of melanoma families were found to harbour genetic alterations at the CDKN2A/ARF gene (Goldstein, 2004). The other gene involved in familial predisposition to melanoma, CDK4 is a proto-oncogene that promotes cell cycle progression by phosphorylating the Rb protein.…”
mentioning
confidence: 99%
“…The patient's significant family history of cancer, including melanoma and pancreatic cancer, and the previous exeresis of a melanoma prompted us to investigate the CDNK2A gene, the main high-risk melanoma gene identified to date (15). This investigation revealed the P48T mutation located in exon 1.…”
Section: Discussionmentioning
confidence: 99%
“…The present report concerns a patient with PTC, CCH-induced hypercalcitoninemia, and normocalcemic hyperparathyroidism, who had previously undergone surgery for a melanoma. This patient displayed the unusual association of germline mutations in two suppressor genes, the RET protooncogene and the CDKN2A, the latter being the main high-risk melanoma gene known to date (15).…”
Section: Introductionmentioning
confidence: 97%